2017
DOI: 10.1093/rb/rbx006
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of nano-sized CuFe2S3: morphology and diverse functional tuning and crystal growth mechanism exploring

Abstract: Ternary chalcogenide compounds are such promising and have been used for much practical applications. As a sort of these compounds, cubanite (CuFe2S3) possess some unique properties which can be used in different fields. In our study, we developed a facile one pot synthesis of CuFe2S3 nanocrystals (NCs) at a low reaction temperature, and achieved a morphology and phase composition tuning of the NCs through changing a variety of precursors and surfactants, meanwhile improved their magnetism and optical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zhang et al reported culturing osteoblast cells on titania nanotubes 38) and varied the size of the titania nanotubes from 50 to 400 nm and compared calcification on a flat titanium surface. In nanotubes approximately 170 nm in diameter, cells adhered most fastest, and the mineralization of the cellular calcium was highest.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported culturing osteoblast cells on titania nanotubes 38) and varied the size of the titania nanotubes from 50 to 400 nm and compared calcification on a flat titanium surface. In nanotubes approximately 170 nm in diameter, cells adhered most fastest, and the mineralization of the cellular calcium was highest.…”
Section: Resultsmentioning
confidence: 99%
“…Cu–Fe–S semiconductors, including CuFeS 2 (chalcopyrite, cp ), CuFe 2 S 3 (isocubanite, cb ), and Cu 5 FeS 4 (bornite, bn ), are earth-abundant low-toxicity thermoelectric materials. In addition, the Cu–Fe–S system can be either a p- or n-type semiconductor depending on the composition. ,, Despite their promising properties, such as low band gap energies and relatively high S values, the ZT values of Cu–Fe–S semiconductors are not very high, mainly because of their low PF values (0.38 mW mK –2 at 625 K for cp , 0.48 mW mK –2 at 663 K for cb , and 0.23 mW mK –2 at 663 K for bn ).…”
Section: Introductionmentioning
confidence: 99%